2020
DOI: 10.1016/j.jiph.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among healthcare providers during coronavirus disease (COVID-19) outbreak in Saudi Arabia

Abstract: Background The novel coronavirus (COVID-19) was recently declared a pandemic by the World Health Organization (WHO). The first confirmed case in Saudi Arabia was announced on March 2, 2020. Several psychiatric manifestations may appear during pandemics, especially among frontline healthcare providers. Objectives This study sought to explore depression and anxiety levels among healthcare providers during the COVID-19 outbreak in Saudi Arabia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
137
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(203 citation statements)
references
References 27 publications
24
137
8
1
Order By: Relevance
“…In our study two thirds of the university students felt tired or low in energy, had trouble sleeping, were depressed or hopeless, and had a loss of interest or pleasure in doing things. This coincides with studies in Saudi Arabia and China which reported a higher prevalence of those symptoms (50,51).…”
Section: Discussionsupporting
confidence: 91%
“…In our study two thirds of the university students felt tired or low in energy, had trouble sleeping, were depressed or hopeless, and had a loss of interest or pleasure in doing things. This coincides with studies in Saudi Arabia and China which reported a higher prevalence of those symptoms (50,51).…”
Section: Discussionsupporting
confidence: 91%
“…Other study in Pakistan, which involved actively COVID-19 frontline health personnel, found higher prevalence rates with moderate-to-severe anxiety and depression scores 5 . Similar results have been found in the study of AlAteeq et al This study revealed that depression and anxiety symptoms are prevalent between COVID-19 health personnel 6 . Depression and anxiety are not prevalent only in health personnel samples, but also in medical students, which correspond to the health personnel in training.…”
Section: Introductionsupporting
confidence: 91%
“…Hence, perceived stress levels and mental health of students during the pandemic require monitoring and in-depth research. students reporting high perceived stress levels than male students (34% vs. 19%) [42]. The prevalence of moderate and severe anxiety symptoms during the pandemic was nearly 4% in Chinese students [43], whereas in Polish university students it was 35% [29].…”
Section: Introductionmentioning
confidence: 90%
“…The 7-item generalized anxiety disorder (GAD-7) scale [42] in the Turkish adaptation [62] is a self-reported measure designed to screen for symptoms following Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) criteria. People rate how often they experienced anxiety symptoms in the two weeks preceding the study on a 4-point Likert scale (0 = not at all, 1 = several days, 2 = more than half the days, and 3 = nearly every day).…”
Section: Methodsmentioning
confidence: 99%